2014
DOI: 10.1109/jbhi.2013.2274460
|View full text |Cite
|
Sign up to set email alerts
|

Potential for Health Screening Using Long-Term Cardiovascular Parameters Measured by Finger Volume-Oscillometry: Pilot Comparative Evaluation in Regular and Sleep-Deprived Activities

Abstract: Abstract-We explored the potential of health screening based on the long-term measurement of cardiovascular parameters using the finger volume-oscillometric technique. An automated instrument made simultaneous measurements of key cardiovascular parameters, including blood pressure, pulse pressure, heart rate, normalized pulse volume as an index of α-adrenalin-mediated sympathetic activity, and finger arterial elasticity. These were derived from finger photoplethysmographic signals during application of cuff pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Subsequently, pulsation signals are converted from the analog to digital form. Since the oscillometric device directly measures the arterial pulsation oscillation, the peak-to-peak intervals of the digitized pulsation signals are used for the calculation of the pulse rate (Yamakoshi et al, 2014). The calculated PR is displayed on the LCD.…”
Section: Oscillometric Methodsmentioning
confidence: 99%
“…Subsequently, pulsation signals are converted from the analog to digital form. Since the oscillometric device directly measures the arterial pulsation oscillation, the peak-to-peak intervals of the digitized pulsation signals are used for the calculation of the pulse rate (Yamakoshi et al, 2014). The calculated PR is displayed on the LCD.…”
Section: Oscillometric Methodsmentioning
confidence: 99%
“…2.2. Both spectral powers were obtained through the FFT (BIMUTUS II, Kissei Comtec Inc., Tokyo, Japan) using 2 14 With this S∕N value, we evaluated the quality of the PPG λ ac waveforms.…”
Section: Procedures and Experimental Designmentioning
confidence: 99%
“…At present, there is interest in using photoplethysmography for the measurement of such physiological indices as pulse rate, 8,9 blood pressure, [10][11][12][13][14] pulse volume, normalized pulse volume as an indication of peripheral vascular tone, [15][16][17] peripheral arterial stiffness, 18 tissue and skin blood flow, 19,20 blood oxygen saturation, 21,22 and cardiac output based on pulse dyedensitometry. 23 In these applications, a variety of wavelengths, from red (610 nm) through to near-infrared (∼1200 nm) have been chosen for the light source, although recent studies have demonstrated some benefits from the use of green light (about 530 nm) to achieve less motion artifact.…”
mentioning
confidence: 99%
“…However, because BP can fluctuate by a significant amount ( Parati et al, 2013 ) both on a beat-by-beat basis and in the long-term, it is important that it is checked frequently, especially in the case of the hypertensive subject. Non-invasive methods for checking beat-by-beat or intermittently obtained BP are preferred, and several are currently available, such as variations of the well-known Riva-Rocci mercury sphygmomanometer, as well as volume oscillometry ( Yamakoshi et al, 1982 ; Parati et al, 2013 ; Yamakoshi et al, 2014 ), volume compensation ( Yamakoshi, Shimazu & Togawa, 1980 ; Matsumura et al, 2017 ) and tonometry ( Hansen & Staber, 2006 ).…”
Section: Introductionmentioning
confidence: 99%